PENGARUH SEKTOR PERTANIAN TERHADAP PEREKONOMIAN INDONESIA - Nuri Rosmika (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2020)
AbstractThis study aims to see the relationship between the agricultural sector and economic growth in Indonesia. This study uses input-output analysis with 2005 Indonesian data. The results show that the agricultural sector has the highest multiplier effect on the Indonesian economy and labor, while the plantation and livestock sectors have the highest effectt on household income. The simulation results show that an increase in government spending on the agricultural sector will increase output. In addition, an increase in investment leads to an increase in output, savings, and investment from the agricultural and non-agricultural sectors. Therefore, if the government wants to increase the output of the agricultural sector, the government must encourage more investment so that it will benefit for Indonesian economy and labor